Culture to Serve Barometer Sustainability of North Sumatera and HANKAMNAS Development in Indonesia - Indra Jaya (Britain International for Academic Research (BIAR) Publisher, 2020)
Malay culture is a unifying tool for the diversity of ethnicity, religion and strata of social life in North Sumatra. This can be traced from: (1) In terms of religious practice manifested in the form of tolerance in carrying out social life among the adherents. (2) In terms of social life, the ability of Malay culture to internalize the diversity of tribes and customs in the differences in the life of social institutions. (3) In terms of community culture, showing the characteristics of millennial generation cultural values ​​as a social phenomenon is actually more likely to be negative.